MAINTAINING THE INFLUENCE OF POWERLESS SURAKARTA HADININGRAT KINGDOM OVER THE SUBJECTS TROUGH RITUAL (The symbolic meaning of Heir Procession On 1 st Muharram at Surakarta Hadiningrat Court) - Idrus Alkaff (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Surakarta Sultanate today no longer has the administrative power in Surakarta and surrounding communities. Surakarta Sultanate has lost its power since the Dutch colonial. The dutch intentionally weaken it. It position subjected to the Chief Resident of Surakarta. From independence until today, The power of sultanate is only to the extent of its palace buildings.Even so its existence is inherent in the heart of Surakarta people and surrounding areas. This paper will try to see the construction of meaning the symbol of ritual Heir Procession held each night 1 Muharram by Kraton Surakarta Sultanate. Through functional approach of culture offered by Geertz, that culture as a system of symbols which is the symbols of and the symbol for, this paper argues that this ritual contains various symbols of spirituality, values, ethics and also an effort to maintain the hierarchical power between the king's palace, nobles and the subjects in the cultural life of Surakarta and surrounding communities.